Morphological changes of UHC steels used as stirrer tools in FSW automations - Sarsilmaz, Furkan; Celik, Busra (Walter de Gruyter Gmbh, 2025)
This study aims to simulate the FSW conditions of fine-grained ultra-high carbon (UHC) steel alloy used as stirrer tool in friction stir welding by external heat treatments. UHC steel is produced using traditional manufacturing methods for experiment. In order to understand the wear behavior of the stirrer tool, to obtain a fine-grained microstructure and to support the formation of softer phases such as spherical cementite, heat treatments of approximately ten thermal cycles were applied to the internal structure. Scanning electron microscopy was used to observe microstructural changes after each cycle and understand the transformation mechanisms. The result showed a gradual decrease in cementite particle size with increasing thermal cycles. Over time, cementite transformed into spherical shapes, reaching an average particle size of approximately 5 mu m. Wear testing revealed that the wear rate is affected by the number of thermal cycles, and the hardness continuously decreases as the number of cycles increases.
Keywords: FSW; UHC steels; microstructure; cementite morphology; wear